STABILISASI TANAH LEMPUNG DENGAN BAHAN KIMIA ASAM FOSFAT SEBAGAI LAPISAN FONDASI JALAN - Ibrahim Ibrahim; Arfan Hasan; Yuniar Yuniar (Politeknik Negeri Sriwijaya, 2013)
Land is a part of the most structure as a foundation that supporting the construction above it. The quality and durability of a construction can’t be separated from the nature of soil, some of them may cause problems. These problems usually occurred because of the unstable soil condition. The settlement that have done so far is to fix the top layer of the road but it doesn’t solve the problem cause unstable road not only the structure on the road but also on the subgrade. The repair on the soft subgrade cause water content can be done with stabilization. This research is analyze about behavior of clays from Soekarno-Hatta Palembang which obtained the density soil maximum and water content optimum with acid phosphate increment as 0% , 2.5% , 5% , 7.5% , 10% and 12.5% of the land, and then do testing of index properties soil and California Bearing Ratio (CBR) test. From the research according to Unifed Soil Classification System (USCS) these soil at this area is included in the OH category, while according to American Association of State Highway an Transportation Officials (AASHTO) these soil is included in the A-7-5 category. The mixture soil with increment acid phosphate than original soil are showed that the liquid limid (LL) and plastic limid (PL) has decreased, it’s mean index plastic (IP) tended to decrease. CBR value with increament of additive tend to increase and attain a peak increase from 7.5% while 10% and 12.5 % decrease.